Quantum inspired computational intelligence : research and applications - Bhattacharyya, Siddhartha; Maulik, Ujjwal; Dutta, Paramartha (Morgan Kaufmann, 2017)
Quantum Inspired Computational Intelligence: Research and Applications explores the latest quantum computational intelligence approaches, initiatives, and applications in computing, engineering, science, and business. The book explores this emerging field of research that applies principles of quantum mechanics to develop more efficient and robust intelligent systems. Conventional computational intelligence-or soft computing-is conjoined with quantum computing to achieve this objective. The models covered can be applied to any endeavor which handles complex and meaningful information.